An analytical model for droplet separation in vane separators and measurements of grade efficiency and pressure drop - Koopmann, Hans K.; Köksoy, Cagatay; Ertunc, Özgür; Lienhart, Hermann; Hedwig, Heinz-Jürgen; Delgado, Antonio (Nuclear Engineering and Design, 2014)
This study investigates the predictive power of analytical models for the droplet separation efficiency of vane separators and compares experimental results of two different vane separator geometries. The ability to predict the separation efficiency of vane separators simplifies their design process, especially when analytical research allows the identification of the most important physical and geometrical parameters and can quantify their contribution. In this paper, an extension of a classical analytical model for separation efficiency is proposed that accounts for the contributions provided by straight wall sections. The extension of the analytical model is benchmarked against experiments performed by Leber (2003) on a single stage straight vane separator. The model is in very reasonable agreement with the experimental values. Results from the analytical model are also compared with experiments performed on a vane separator of simplified geometry (VS-1). The experimental separation efficiencies, computed from the measured liquid mass balances, are significantly below the model predictions, which lie arbitrarily close to unity. This difference is attributed to re-entrainment through film detachment from the last stage of the vane separators. After adjustment for re-entrainment effects, by applying a cut-off filter to the outlet droplet size spectra, the experimental and theoretical outlet Sauter mean diameters show very good agreement. A novel vane separator geometry of patented design (VS-2) is also investigated, comparing experimental results with VS-1. Experimental separation efficiencies based on recorded mass flow balances are very similar for both geometries. However, based on an analysis of the outlet droplet size spectra, VS-2 outperforms VS-1. It is concluded that re-entrainment effects cloud the performance of VS-2 and that the perforations in the wall sections of VS-2 are not very effective. Pressure drop measurements performed on both geometries reveal that the pressure drop for VS-2 is higher than for VS-1 by a factor of almost two for gas velocities up to 10 m/s. © 2014 Elsevier B.V.
UnivIS-Import:2015-04-14:Pub.2014.tech.ITC.stmmec.ananal

Boundary layer measurements of the flow along a streamwise-oriented circular cylinder using particle tracking velocimetry - Näger, Christoph; Wachter, Florian; Lienhart, Hermann; Czwielong, Felix; Riedel, Jörg; Becker, Stefan (International Journal of Heat and Fluid Flow, 2023)
Particle tracking velocimetry (PTV) measurements of an axisymmetric turbulent boundary layer (ATBL) around a long circular cylinder in axial flow were carried out in a large-scale water tunnel at different velocities and at different measurement positions along the cylinder. A relatively thick ATBL developed with ratios of delta/a between 4.6 and 8.1 and a/delta_nu between 313 and 1027, where delta is the boundary layer thickness, delta_nu the viscous length scale and a the cylinder radius. At ratios of delta/a above unity and a/delta_nu above 250, transverse curvature effects are known to influence the boundary layer in the outer region. This was observed in the measured mean velocity profiles as the profiles fall below the planar logarithmic law of the wall. Shape factors close to unity with a rather full velocity profile were determined that explain the relatively high skin friction coefficient known to be present for such ATBL flows. Additionally, measurements of the turbulence intensity and Reynolds stress profiles are presented. The non-intrusive PTV measurement approach allowed to gather near-wall velocity data down to a wall-distance below 10 wall-units. The present study provides valuable information regarding ATBL flows along streamwise-oriented cylinders in the flow regime indicated above by the ranges of delta/a and a/delta_nu . In particular, it fills a gap in the literature as far as experimentally obtained higher-order statistical quantities are concerned, such as root-mean-square velocity fluctuations and Reynolds stresses.<br
Keywords: Axisymetric turbulent boundary layer; Axial cylinder flow; Particle tracking velocimetry; Towed array sonar; Marine seismic streamer; Water tunnel

Detection of artefact reduced PIV data in the flow around bionic specimen - Zima-Kulisiewicz, Bogumila Ewelina; Lienhart, Hermann; Rauh, Cornelia; Delgado, Antonio; Krupczynski, Philipp; Schuster, Stefan (Proceedings der 16. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik, 2008)
UnivIS-Import:2017-12-18:Pub.2008.tech.ITC.stmmec.detect

Effect of the Motion Pattern on the Turbulence Generated by an Active Grid - Herbert, Meike; Skeledzic, Tanja; Lienhart, Hermann; Ertunc, Özgür (Notes on Numerical Fluid Mechanics and Multidisciplinary Design, 2021)
In the field of turbulence research, many experiments are performed using turbulence generated under reproducible conditions. In the past mostly static grids having a fixed blockage were adopted, but in order to generate turbulence with high intensity and high turbulence Reynolds numbers, so called active grids can be used. Therefore, an experimental study has been carried out to investigate the effect of the motion pattern on the turbulence generated by an active grid with individually controllable paddles in the wind tunnel. Measurements were performed using the hot-wire technique. In comparison to former experiments, modifications of the active grid had been made concerning the arrangement of the paddles. The results show that the homogeneity of the turbulence could be improved using the modified grid. Turbulence Reynolds numbers could reach values up to 540. In order to produce even higher integral time scales or higher turbulence Reynolds numbers, synchronous movement of adjacent paddles was tested but did not show the intended improvements. In this paper, the results of the experimental study are presented in more detail.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Active grid; Experimental study; Turbulence

Evolution of transitional structures from puff to slug through multiple splitting in a pipe flow at low Reynolds number - Krauß, Jens; Ertunc, Özgür; Ostwald, Christina; Lienhart, Hermann; Delgado, Antonio (Journal of Physics : Conference Series, 2011)
During laminar-to-turbulent transition in low Reynolds pipe flows, three main types of flow structures occur: traveling waves and the turbulent flow structures, namely puffs and slugs. In the present work, detailed experiments on the probability of occurrence and propagation speed of puffs, splitting puffs and slugs were conducted with the transition pipe-flow facility of LSTM-Erlangen. During the investigations, fully developed laminar pipe flow was triggered by an iris diaphragm with a pre-defined amplitude and lapse time. Different types of single and multiple puffs are classified and the probability of their occurrence as well as their propagation speed at the end of pipes with different lengths are evaluated.
UnivIS-Import:2015-03-09:Pub.2011.tech.ITC.stmmec.evolut_4

Experimental investigation of viscous drag reduction by flow control of laminar to turbulent transition using microgroove surface pattern - Jovanovic, Jovan; Frohnapfel, Bettina; Lienhart, Hermann; Delgado, Antonio (Proceedings of the 8th International ERCOFTAC Symposium on Engineering Turbulence Modelling and Measurements, 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.ITC.stmmec.experi_1

Kinematics and hydrodynamics of undulatory fin motion of seahorse - Zima-Kulisiewicz, Bogumila Ewelina; Lienhart, Hermann; Rauh, Cornelia; Delgado, Antonio; Botello Payro, Emanuela; Krupczynski, Philipp; Schuster, Stefan (Proceedings der 17. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik", 2009)
UnivIS-Import:2017-12-18:Pub.2009.tech.ITC.stmmec.kinema

Microflow-based control of near-wall fluctuations for large viscous drag reduction - Jovanovic, Jovan; Srikantharajah, Rubitha; Lienhart, Hermann; Delgado, Antonio; Frohnapfel, Bettina; Jovanović, Djordje (Microfluidics and Nanofluidics, 2011)
The stabilizing effect of microgroove surface morphology on viscous drag reduction was studied experimentally in the inlet region of a plane channel flow. The stabilization is thought to be due to the ability of a microgrooved surface pattern to suppress the velocity fluctuations in the spanwise direction on a restricted portion of the wetted surface, which prevents vorticity development at the wall and consequently across the entire flow field. This smart microflow control strategy, which works successfully only under very particular circumstances, was implemented in a microgroove-modified channel flow in which the front part has a microgrooved surface topology. The results of pressure drop measurements indicate that microgrooved surfaces can effectively stabilize laminar boundary layer development, leading to a significant reduction in the viscous drag. In the rear flat part of the microgroove-modified channel test section, a maximum drag reduction of DR ≃ 35% was measured. This corresponds to an overall drag reduction of DR ≃ 16% at a length Reynolds number of Re x ≃ 10 6: The drag reduction effect persisted in a narrow range of flow velocities and for the reported experimental conditions corresponds to microgroove dimensions between 1.5 and 2.5 viscous length-scales. © Springer-Verlag 2011.
UnivIS-Import:2015-03-09:Pub.2011.tech.ITC.stmmec.microf
Keywords: microflow; drag; control

Probability of occurrence of the turbulent flow structures in transitional pipe flows - Krauß, Jens; Ertunc, Özgür; Ostwald, Christina; Lienhart, Hermann; Delgado, Antonio (Notes on Numerical Fluid Mechanics and Multidisciplinary Design. New Results in Numerical and Experimental Fluid Mechanics VIII, 2013)
During laminar-to-turbulent transition in low Reynolds number (Re) pipe flows, two main types of turbulent flow structures occur: puff and slug. Puff structures can be initiated by inducing short-time, large amplitude localized disturbances in the pipe. They are equilibrium structures, i.e. they do not grow. Furthermore, they dissipate at random as they travel along the pipe. Therefore, they represent an incomplete relaminarization process. However, lifetimes of puffs diverge or attain very high values at some critical Re. At Reynolds numbers higher than this critical value, disturbances evolves from puff to slug through multiple splitting. In other words, the flow structures start to grow and fill the space. During this evolution, many types of structures occur. This evolution is associated with the onset of turbulence. In the present work, detailed experiments on the probability of occurrence and propagation speed of puffs, splitting puffs and slugs were conducted. During the investigations, fully developed laminar pipe flow was disturbed by an iris diaphragm with a pre-defined amplitude and duration. Different types structures, such as single puff, splitting puff and slugs, are classified and the probability of their occurrence at the end of pipes with different lengths are evaluated. © 2013 Springer-Verlag Berlin Heidelberg.
UnivIS-Import:2015-04-20:Pub.2013.tech.ITC.stmmec.probab_8

Selbstinduzierte Schwingungen zwei- und dreidimensionaler Strukturen in turbulenten Strömungen - Gomes, Jorge; Lienhart, Hermann; Delgado, Antonio (Proceedings der 17. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik, 2009)
UnivIS-Import:2015-04-16:Pub.2009.tech.ITC.stmmec.selbst_1

The evolution of transitional flow structures along a 3200 d pipe in the decay and growth regimes - Ertunc, Özgür; Krauß, Jens; Lienhart, Hermann; Schweiger, H.; Weber, Horst; Delgado, Antonio (ETC 2013 - 14th European Turbulence Conference, 2013)
The evolution of transitional flow structures along a 3200 D pipe in the decay and growth regimes are measured in a 3200 D structure tracking pipe flow facility. We report the statistics of the evolution for the probability of occurrence, characteristic lifetime, speed and length of the structures.
CRIS-Team Scopus Importer:2020-03-17

The structure of turbulence in a swirling pipe flow - Jovanovic, Jovan; Pashtrapanska, Mira; Lienhart, Hermann; Delgado, Antonio (PAMM, 79th Annual Meeting of the International Association of Applied Mathematics and Mechanics (GAMM), Bremen 2008, 2008)
UnivIS-Import:2015-04-16:Pub.2008.tech.ITC.stmmec.thestr

Toward design of the antiturbulence surface exhibiting maximum drag reduction effect - Krieger, Veronika; Peric, Robinson; Jovanovic, Jovan; Lienhart, Hermann; Delgado, Antonio (Journal of Fluid Mechanics, 2018)
The flow development in a groove-modified channel consisting of flat and grooved walls was investigated by direct numerical simulations based on the Navier-Stokes equations at a Reynolds number of based on the full channel height and the bulk velocity. Simulations were performed for highly disturbed initial flow conditions leading to the almost instantaneous appearance of turbulence in channels with flat walls. The surface morphology was designed in the form of profiled grooves aligned with the flow direction and embedded in the wall. Such grooves are presumed to allow development of only the statistically axisymmetric disturbances. In contrast to the rapid production of turbulence along a flat wall, it was found that such development was suppressed over a grooved wall for a remarkably long period of time. Owing to the difference in the flow structure, friction drag over the grooved wall was more than 60Â % lower than that over the flat wall. Anisotropy-invariant mapping supports the conclusion, emerging from analytic considerations, that persistence of the laminar regime is due to statistical axisymmetry in the velocity fluctuations. Complementary investigations of turbulent drag reduction in grooved channels demonstrated that promotion of such a state across the entire wetted surface is required to stabilize flow and prevent transition and breakdown to turbulence. To support the results of numerical investigations, measurements in groove-modified channel flow were performed. Comparisons of the pressure differentials measured along flat and groove-modified channels reveal a skin-friction reduction as large as owing to the extended persistence of the laminar flow compared with flow development in a flat channel. These experiments demonstrate that early stabilization of the laminar boundary layer development with a grooved surface promotes drag reduction in a fully turbulent flow with a preserving magnitude as the Reynolds number increases.
UnivIS-Import:2018-09-05:Pub.2018.tech.ITC.stmmec.toward
Keywords: drag reduction; turbulence control; turbulence modelling

Verfolgung transitionaler Strömungstrukturen bei kleinen Reynoldszahlen in einer 3200D Rohrmessstrecke - Krauß, Jens; Ertunc, Ozgur; Lienhart, Hermann; Schweiger, H.; Weber, Horst; Delgado, Antonio (Proceedings der 22. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik", 2014)